GRAMMAR MATTERS: A STUDY OF FREE WRITING PERFORMANCE OF THE SIXTH SEMESTER STUDENTS, FBIB-UNISBANK - Sugeng Purwanto (Dinamika Bahasa dan Budaya, 2017)
The current study explores possible errors or mistakes committed by the sixth semester students of  English Letters Study Program, FBIB, Stikubank University  in order to position the students’ levels of writing performance against grammatical violation. Twenty students participated in the research by writing free compositions. Most of them wrote academic essays as they had thought that it was a good writing exercises prior to their main assignments—writing academic papers as their own final project.  Grammarly software application was used to assess the students’ writing. The findings indicated that the students performed considerably well in writing practice, yielding grades-A (65%), grades-B (20%) and grades-C (15%). In practice, grades-C shall have to retake the test for a little bit below the passing grades (but ‘pass conceded’).  Grades-D and E are ‘Failed’ grades. The dominant errors, according to Grammarly,  were of (1) possibly confused prepositions, (2) missing comas, after introductory phrases, and (3) redundant indefinite articles. It is therefore recommended that the students keep practice writing since all grammatical features had been covered in their previous grammar classes. Keywords: writing performance, gramatical violation, Grammarly software application